CITES and beyond: Illuminating 20 years of global, legal wildlife trade - Andersson, Astrid Alexandra; Tilley, Hannah B.; Lau, Wilson; Dudgeon, David; Bonebrake, Timothy C.; Dingle, Caroline (Global ecology and conservation, 2021)
Nature has the potential to provide wide-ranging economic contributions to society – from ecosystem services to providing income to communities via fair trade of resources. Unsustainable trade in wildlife, however, threatens biodiversity and its ability to support communities and a functioning planet. It is therefore important to have clear systems in place for tracing traded wildlife. Monitoring legal wildlife trade in all species is as important as it is for trade in protected species, since flows of the legal trade correlate with, and provide cover for, illegally traded wildlife. The majority of wildlife trade research is focused on species listed in the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). The concurrent, considerably larger legal wildlife trade in both CITES and non-CITES-listed species, however, remains unexamined – despite the fact that if mismanaged, it can lead to over-exploitation. Here we analyzed 20 years of data from the UN Comtrade database, aiming to detail the scale, composition, and trends across all taxa of wildlife traded legally, and to indicate opportunities for improvement. From 1997 to 2016 the value of this trade totaled between US$2.9 and 4.4 trillion. Of this, $2.9 trillion wildlife was traded under “specific” codes that specify taxonomic Order and below, while around $1.4 trillion was traded under “broad” codes that declare wildlife to taxonomic Class and above. The top 10 trading nations/territories accounted for 51.4% of the total value of wildlife traded. The top commercial categories for wildlife trade were seafood (82%), furniture (7%), and fashion (furs and hides) (6%). In these three major categories, vague commodity codes such as “Fish”, “Tropical wood”, and “Other furs” were used to declare 23%, 24% and 26% of items traded, respectively – despite encompassing thousands of species. This lack of granularity imperils biodiversity as trade cannot be comprehensively monitored. We recommend a review of what species are traded under these broad code descriptions, and a distillation of codes to taxonomic Family or Genus level in the next HS Code review period, particularly in the pet, traditional Chinese medicine and furniture categories. In addition, interdisciplinary research into legal wildlife trade should be increased to provide forensic, policy, economic and social solutions to improve trade management. •Legal wildlife trade remains largely unexamined, despite its scale.•UN Comtrade data reveal that legal wildlife trade was worth between US$2.9 and 4.4 trillion from 1997-2016.•Seafood, furniture and fashion were the largest categories of traded commodities.•34% of trade declared under overly broad codes (taxonomic Class and above).•Distillation of HS Codes would increase traceability and help monitor trade.